2015
DOI: 10.1371/journal.pone.0128981
|View full text |Cite
|
Sign up to set email alerts
|

A New Synthetic Amphiploid (AADDAA) between Gossypium hirsutum and G. arboreum Lays the Foundation for Transferring Resistances to Verticillium and Drought

Abstract: Gossypium arboreum, a cultivated cotton species (2n = 26, AA) native to Asia, possesses invaluable characteristics unavailable in the tetraploid cultivated cotton gene pool, such as resistance to pests and diseases and tolerance to abiotic stresses. However, it is quite difficult to transfer favorable traits into Upland cotton through conventional methods due to the cross-incompatibility of G. hirsutum (2n = 52, AADD) and G. arboreum. Here, we improved an embryo rescue technique to overcome the cross-incompati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…Cotton is one of the most economically important crops worldwide (Kalivas et al 2011). Gossypium arboreum (diploid) is drought tolerant, and a better candidate for studying drought tolerance-related genes than G. hirsutum (tetraploid) (Chen et al 2015). Jasmonic acid regulates plant defense activities by inducing the expression of TIFY genes, which forms part of a negative feedback loop biosynthesis pathway and a signal transduction pathway that controls JAZ protein levels in response to JA and environmental stress (Song et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Cotton is one of the most economically important crops worldwide (Kalivas et al 2011). Gossypium arboreum (diploid) is drought tolerant, and a better candidate for studying drought tolerance-related genes than G. hirsutum (tetraploid) (Chen et al 2015). Jasmonic acid regulates plant defense activities by inducing the expression of TIFY genes, which forms part of a negative feedback loop biosynthesis pathway and a signal transduction pathway that controls JAZ protein levels in response to JA and environmental stress (Song et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The comparison of synthetic and natural allopolyploids in cotton revealed that genome merger, rather than genome doubling or subsequent evolution, greatly alters expression levels due to cis‐ regulatory variation (Chaudhary et al, 2009); these results have been supported by both microarray and RNA‐sequencing analyses (Yoo et al, 2014). Finally, as an economically significant crop, novel synthetic allopolyploids are being developed rapidly to provide additional genetic materials for current breeding programs (Zhang et al, 2014b; Liu et al, 2015; Chen et al, 2015). Despite their lack of a natural counterpart, these novel synthetics can provide lineage‐specific biological replicates for understanding the impact of polyploidy in multiple genetic lines.…”
Section: Comparing Systemsmentioning
confidence: 99%
“…Several obstacles exist in the process of cotton distant hybridization breeding using wild relatives, such as interspecific cross incompatibility, interspecific hybrid F 1 sterility, low rates of genetic recombination giving rise to linkage drag, and challenges in the reliable identification and characterization of the progenies of interspecific hybridization in mitotic and meiotic cells due to the small size of chromosomes in cotton (2n = 52). Our previous reports showed that the interspecific cross incompatibility can be alleviated via embryo rescue and F 1 sterility can be overcome by chromosome doubling through treatment with colchicines [ 28 ]. Identification and characterization of alien chromosomes in mitotic and meiotic cells of the progenies of interspecific hybridization can be easily achieved through a combination of GISH and molecular marker (SSR) analysis [ 5 , 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%